Sustainable Healthcare Depends on Good Governance Practices. Issue 3 (2023) - Greenhill, Richard G.; Khalil, Merette
Abstract : Effective leadership and governance are at the heart of creating and maintaining resilient health systems. COVID-19 exposed a plethora of issues in its wake, most notably the need to plan for resilience. Facing threats that swirl around climate, fiscal solvency, and emerging infectious diseases, healthcare leaders are challenged to think broadly on issues that affect operational viability. The global healthcare community has offered numerous approaches, frameworks, and criteria to assist leaders in creating strategies for better health governance, security, and resilience. As the world exits the worst of the pandemic, now is the time to plan for the sustainability of those strategies. Based on guidance developed by the World Health Organization, good governance is one key to sustainability. Healthcare leaders who develop measures to assess and monitor progress toward strengthening resilience can achieve sustainable development goals.